„Boże… / czemu nas opuściłeś” – odwołania religijne w tomiku Z ziemi do nieba Władysława Grabana - Rychter, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The paper discusses religious references in poems from Z ziemi do nieba, a poetry book published by Władysław Graban in 2015. These references appear at a number of language levels: lexis, orthography, phraseology (including paraphrases of Bible verses). There are direct references to the Old Testament (lexemes, phraseological units of biblical origin) and indirect references to biblical motifs and themes.